A clinical and genetic study of campomelic dysplasia. Issue 6 (June 1995) - Mansour, S; Hall, C M; Pembrey, M E; Young, I D
Abstract : Campomelic dysplasia (CMD) is a rare skeletal disorder that is usually lethal. It is characterised by bowing of the lower limbs, severe respiratory distress, and many of the chromosomal (XY) males show sex reversal. Because of a number of reports of familial campomelic dysplasia it is considered to be inherited in an autosomal recessive manner. In this study, details of 36 patients with campomelic dysplasia were collected from genetic centres, radiologists, and pathologists in the United Kingdom. The chromosomal sex ratio was approximately 1:1. There was a preponderance of phenotypic females owing to sex reversal. Three quarters of the chromosomal males were sex reversed or had ambiguous genitalia. Three cases are still alive, two with chromosomal rearrangements involving chromosome 17q. The majority of the others died in the neonatal period. The 36 index cases had 41 sibs of whom only two were affected. Formal segregation analysis gave a segregation ratio of 0.05 (95% CI approximately 0.00 to 0.11). This excludes an autosomal recessive mode of inheritance. The data suggest a sporadic, autosomal dominant mode of inheritance. Patients with a chromosomal rearrangement involving 17q (q23.3-q25.1) show a milder phenotype. The molecular mechanism for the difference is still unknown.